Biomechanical studies on running the 400 m hurdles - Iskra, J.; Coh, M. (Human Movement, 2011)
Purpose. Biomechanical research conducted on hurdling are the basis for analysis of technique used in running disciplines. However, the 400 m hurdle run is an athletic discipline rarely subjected to individual biomechanical study. The aim of this study was to introduce the various forms of biomechanical studies on this difficult-to-quantify athletic event. Methods. In this study, 64 biomechanical articles were assessed, each covering various topics such as kinematics, dynamics, accelometrics and rhythm knowledge in the both the men`s and women`s 400 m hurdles. This was conducted with regard to the specificity of studies on the 400 m hurdles, including their types, methods and difficulties. The characteristics of the study were divided, among others, into: physiological effort, centrifugal force, dynamics of movement, stride rhythm, the level of abilities, laterality and type of body build. Results. Numerous sources allowed the creation of a general outline of present biomechanical studies. Conclusions. Within the context of the conducted analysis on the present state of biomechanical analysis on the 400 m hurdles, a number of basic principles were outlined that could determine the effectiveness of future research possibilities for scientists on the 400 m hurdles.